Health Care at the Crossroads - Vinall, Maria (MD Conference Express, 2014)
During the Emery A. Rovenstine Memorial Lecture, the state of health care in the United States was discussed. The Lecture stressed that health care is changing at an enormous rate and it is imperative for anesthesiologists to change and adapt to this new dynamic environment and or risk losing their contracts or jobs to competitors.